Comparative analysis of stripe rust resistance in seedling stage and Yr gene incidence in spring and winter wheat from Xinjiang, China - Lai, Hanlin; Shen, Yuyang; Yang, Hong; Fernando, Dilantha W. G.; Ren, Chenrong; Deng, Feifei; Lu, Yi; Sun, Na; Chen, Li; Li, Guangkuo; Wang, Huiqing; Gao, Haifeng; et al. (Frontiers in Plant Science, 2024)
Stripe rust, caused by the fungus Puccinia striiformis f.sp. tritici (Pst), poses a significant threat to global wheat production. This study aims to analyze the distribution of stripe rust resistance genes, characterize resistance phenotypes at the seedling stage of 137 spring and 149 winter wheat varieties in Xinjiang, China, and discern differences in resistance between spring and winter wheat varieties. We used various Pst races (CYR23, CYR29, CYR31, CYR32, CYR33, CYR34) to characterize seedling resistance of spring and winter wheat varieties and to correlate resistance to the presence of wheat resistance genes (Yr5, Yr9, Yr10, Yr15, Yr17, Yr18, Yr26, Yr41, Yr80, Yr81) using molecular markers. Among spring wheat varieties, 62, 60, 42, 26, 51, and 24 varieties exhibited resistance to CYR23, CYR29, CYR31, CYR32, CYR33, and CYR34, respectively, with four varieties resistant to all varieties. Among winter wheat varieties, 66, 32, 69, 26, 83, 40 varieties demonstrated resistance to CYR23, CYR29, CYR31, CYR32, CYR33, and CYR34, respectively, with four varieties resistant to all varieties. Molecular testing revealed that, in spring wheat, 2, 17, 21, 61, 10, 0, 10, 79, and 32 varieties carried Yr9, Yr10, Yr15, Yr17, Yr18, Yr26, Yr41, Yr80, and Yr81 genes, respectively. In winter wheat, 40, 20, 7, 143, 15, 1, 6, 38, and 54 varieties carried Yr9, Yr10, Yr15, Yr17, Yr18, Yr26, Yr41, Yr80, and Yr81 genes, respectively. Notably, winter wheat exhibited a significantly higher resistance frequency than spring wheat, particularly in the incidence of Yr9, Yr10, Yr17, Yr18, and multi-gene combinations. In summary, this study provides information on seedling stage resistance to stripe rust 286 Xinjiang wheat varieties, elucidates the distribution of resistance genes in this population, and offers a mechanistic basis for breeding durable resistance in wheat varieties from Xinjiang.